Measurement of the running of the electromagnetic coupling at large momentum-transfer at LEP - Dova, María Teresa (2005)
The evolution of the electromagnetic coupling, α, in the momentum-transfer range 1800 GeV2 < −Q2 < 21600 GeV2 is studied with about 40 000 Bhabha-scattering events collected with the L3 detector at LEP at centre-of-mass energies √s = 189–209 GeV. The running of α is parametrised as: α(Q2)=α01−CΔα(Q2), where α0 ≡ α(Q2 = 0) is the fine-structure constant and C = 1 corresponds to the evolution expected in QED. A fit to the differential cross section of the e+e− → e+e− process for scattering angles in the range |cos θ| < 0.9 excludes the hypothesis of a constant value of α, C = 0, and validates the QED prediction with the result: C = 1.05 ± 0.07 ± 0.14, where the first uncertainty is statistical and the second systematic.